2004
DOI: 10.1099/mic.0.27467-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacillus subtilis  -glutamyltransferase and its involvement in the degradation of capsule poly- -glutamate

Abstract: During early stationary phase, Bacillus subtilis NAFM5 produces capsular poly(c-glutamic acid) (cPGA, 2610 6 Da), which contains D-and L-glutamate, and then degrades it during late stationary phase. The c-glutamyltransferase (EC 2.3.2.2; GGT) of this strain successively hydrolysed cPGA from the amino-terminal end, to yield both D-and L-glutamate. This enzyme was specifically synthesized during the stationary phase through transcriptional activation of the corresponding ggt gene by the ComQXPA quorum-sensing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 42 publications
3
93
0
Order By: Relevance
“…The function also depends on whether the c-PGA is peptidoglycan bound or released. If the c-PGA is peptidoglycan bound, it may help confer virulence or it can act as a source of glutamate under conditions of starvation (Kimura et al, 2004;Kocianova et al, 2005). If it is released into the environment, c-PGA can help the organism survive under adverse conditions (McLean et al, 1990).…”
Section: Function Of C-pgamentioning
confidence: 99%
See 4 more Smart Citations
“…The function also depends on whether the c-PGA is peptidoglycan bound or released. If the c-PGA is peptidoglycan bound, it may help confer virulence or it can act as a source of glutamate under conditions of starvation (Kimura et al, 2004;Kocianova et al, 2005). If it is released into the environment, c-PGA can help the organism survive under adverse conditions (McLean et al, 1990).…”
Section: Function Of C-pgamentioning
confidence: 99%
“…RacE is a cytosolic enzyme with a high selectivity for glutamic acid and a preference for L-glutamic acid (Thorne et al, 1955;Buescher & Margaritis, 2007). According to Kimura et al (2004), racE was only important for growth in complex medium, whereas yrpC was found to be active when cells were grown on minimal medium. Neither of the two glutamate racemase genes was found to be responsible for the synthesis of c-PGA even though both seemed essential for D-glutamate catabolism (Kimura et al, 2004).…”
Section: Mechanism Of Synthesis Of C-pgamentioning
confidence: 99%
See 3 more Smart Citations